Therapeutic potential of Litsea cubeba essential oil in modulating inflammation and the gut microbiome - Xia, Liqiong; Li, Ran; Tao, Ting; Zhong, Ruimin; Du, Haifang; Liao, Ziling; Sun, Zhanghua; Xu, Changqiong (Frontiers in Microbiology, 2023)
Inflammation, a sophisticated and delicately balanced physiological mechanism, is paramount to the host's immunological defense against pathogens. However, unfettered and excessive inflammation can be instrumental in engendering a plethora of chronic ailments and detrimental health repercussions, notably within the gastrointestinal tract. Lipopolysaccharides (LPS) from bacteria are potent endotoxins capable of instigating intestinal inflammation through the disruption of the intestinal epithelial barrier and the stimulation of a pro-inflammatory immune response. In this study, we sought to investigate the influence of Litsea cubeba essential oil (LCEO) on LPS-induced intestinal inflammation and associated changes in the gut microbiota. We investigated the therapeutic potential of LCEO for gut health, with particular emphasis on its gut protective properties, anti-inflammatory properties and modulation of the gut microbiome. LCEO exhibited protective effects on colonic tissue by protecting crypts and maintaining epithelial integrity, and anti-inflammatory properties by reducing TNF-α, IL-6 and IL-1β levels in the liver and intestine. Citral, a major component of LCEO, showed robust binding to IL-1β, IL-6 and TNF-α, exerting anti-inflammatory effects through hydrogen bonding interactions. Using community barplot and LEfSe analyses, we detected significant variation in microbial composition, identified discrete biomarkers, and highlighted the influence of essential oils on gut microbial 2 communities. Our research suggests that LCEO may be a promising natural compound for ameliorating diarrhoea and intestinal inflammation, with potential implications for modulating the gut microbiome. These observations provide invaluable insight into the potential therapeutic role of LCEO as a natural anti-inflammatory agent for treating intestinal inflammatory disorders, particularly in the setting of a dysregulated immune response and altered gut microbiota. Furthermore, our findings highlight the need to understand the complex interplay between the host, the gut microbiome and natural products in the context of inflammatory diseases.